MIF reflects tissue damage rather than inflammation in post-cardiac arrest syndrome in a real life cohort. (March 2016) - Pohl, Julia; Rammos, Christos; Totzeck, Matthias; Stock, Pia; Kelm, Malte; Rassaf, Tienush; Luedike, Peter
Abstract: Introduction: Following successful resuscitation from cardiac arrest (CA), neurological impairment and other types of organ dysfunction cause significant morbidity and mortality—a condition termed post-cardiac arrest syndrome. Whole-body ischemia/reperfusion with oxygen debt activates immunologic and coagulation pathways increasing the risk of multiple organ failure and infection. We here examined the role of the pro-inflammatory cytokine macrophage migration inhibitory factor (MIF) in post-cardiac arrest syndrome. Methods: MIF plasma levels of n = 16 patients with return of spontaneous circulation (ROSC) after CA were assessed with a previously validated method and compared to markers of systemic inflammation and cellular damage. ICU patients without former CA and healthy volunteers served as controls. Results: MIF levels in patients after ROSC were higher compared to those in healthy volunteers and ICU patients without CA. Kaplan–Meyer analysis revealed a distinctly elevated mortality since day one that further increased towards an elevated 60-days-mortality in patients with high plasma MIF. ROC curve identified plasma MIF as a predictor for mortality in patients after CA. Correlation with inflammatory parameters revealed that high MIF levels did not mirror post CA inflammatory syndrome, but distinctive cellular damage after ROSC as there were strong correlations with markers of cellular damage like LDH and GOT/GPT. Conclusion: High MIF levels were associated with elevated 60-days-mortality and high MIF predicted mortality after CA. We found a close relation between circulating MIF levels and cellular damage, but not with an inflammatory syndrome.